Pengaruh Brand Image, E-Service Quality, E-Wom terhadap Brand Switching pada Pengguna Kartu Axis di Kota Bandung - Bella Yugistira; Ida Farida Oesman; Indri Ferdiani Suarna (Journal of Management and Bussines (JOMB), 2024)
This research was conducted at PT. XL Axiata Tbk with the aim of understanding the influence of brand image, electronic service quality and e-WOM on users' tendency to switch brands. A quantitative approach was used in this research involving 400 respondents as samples. The non-propability sampling method was used by distributing questionnaires to Axis card users in Bandung City. The research results show that brand image, electronic service quality, and e-WOM have a positive and significant influence on users' tendency to switch brands. Simultaneously, these three variables also have a positive and significant effect on users' tendency to switch brands. In conclusion, these findings provide valuable insight for PT. XL Axiata Tbk in designing more effective marketing and service strategies to maintain and increase their Axis customer base. Keywords: Brand Image, Brand Switching, E-Service Quality, E-Wom